Management of fetal dystocia caused by carpal flexion in ewe: A case report (Journal of Advanced Veterinary and Animal Research, 2015)
Dystocia or difficulty in parturition in a ewe may need veterinary assistance for the successful parturition. An adult ewe weighing 30 kg was presented to the Hospital of Veterinary Medicine, Universiti Putra Malaysia with the history of difficulty in giving birth. Physical examination of the ewe revealed that the animal was weak and in recumbent position. Head of a dead fetus was observed as protruding out from the vulva region. Through physical evaluation of the ewe by per vaginal examination, the condition was diagnosed as fetal dystocia. Treatment and management plans given to the ewe were episiotomy and manipulative delivery of the dead fetus via mutation and traction method. Post-operative treatment was given with Flunixin meglumine (dosed at 2.2 mg/kg bwt) for 3 days, and Norodine (dosed at 1 mL/16-kg bwt) once intramuscularly. The case was completely cured after 2 weeks. The risk of losing the lamb as well as the ewe increases with delay in treatment of dystocia.http://dx.doi.org/10.5455/javar.2015.b70